Analysis of Blasting Vibration Effect of Railway Tunnel and Determination of Reasonable Burial Depth. (16th September 2022) - Wang, Hailong; Zhao, Yan; Shan, Renliang; Tong, Xiao; Liu, Dong
Abstract : Based on specific examples of underpass tunnel blasting, field measurements, and numerical simulation studies are carried out. According to the results of the blasting vibration data measured on-site, a regression model of the blasting vibration velocity is established. Based on the wavelet packet energy spectrum analysis method, the effect of frequency on the vibration response intensity is studied. In addition, the maximum charge per delay allowed for tunnel blasting is obtained by formula inversion. Relying on ANSYS/LS-DYNA to establish a three-dimensional numerical model, the accuracy of numerical simulation can be checked by the measured vibration data. The results show that the numerical simulation has high precision and can meet the subsequent analysis needs. Using numerical simulation, the variation law of the vibration response characteristics of ground blasting under different tunnel burial depths is studied. The analysis results show that with increasing tunnel burial depth, the ground blasting vibration velocity decays exponentially. According to the corresponding specification of blasting vibration, a reasonable value range of the buried depth of the underpass tunnel can be obtained. The research ideas and methods introduced can be used for reference for similar railway tunnel blasting control and railway tunnel route selection.